Molecular Characterization of the Insulin-Like Androgenic Gland Hormone in the Swimming Crab, Portunus trituberculatus, and Its Involvement in the Insulin Signaling System - Jiang, Qinghua; Zheng, Hongkun; Zheng, Liang; Wang, Yaojing; Wang, Mengen; Xie, Xi; Zhu, Dongfa (Frontiers in Endocrinology, 2020)
The insulin-like androgenic gland hormone (IAG) is mainly produced in the androgenic gland (AG) of the male crustaceans, and is a crucial regulator in male sexual differentiation. In the current study, the full-length cDNA of IAG in the swimming crab, Portunus trituberculatus (Pt-IAG), was cloned and characterized. Similar to other reported IAGs, the deduced amino acid sequence of Pt-IAG was consist of signal peptide, B chain, C peptide and A chain, containing 6 conserved cysteines that form two inter-chain disulfide bonds and one intra-B chain disulfide bond. Tissue distribution analysis suggested that the Pt-IAG cDNA was highly expressed in the AG, and was slightly expressed in several other tissues. A short-term silencing of PtIAG with double-stranded RNA was found to reduce the transcript levels of insulin receptor (Pt-IR) and insulin-like growth factor-binding protein (Pt-IGFBP), suggesting the Pt-IAG might perform its biological function through the insulin family-based signaling system. Bilaterally eyestalk ablation induced the expression of Pt-IAG in AG at 4 and 7 d after surgery, while the transcript levels of Pt-IR in AG and testis and Pt-IGFBP in muscle, testis, and thoracalia ganglia were significantly decreased from 1 d after surgery. The results suggested that the Pt-IR and Pt-IGFBP might also be the targets of eyestalk neuropeptides, and responded to the ESA independent of IAG regulation.